Analysis of pre-combustion chamber in single cylinder engine performance with natural gas fuel - Muhamad Tajuddin, Khairil Amri (2024)
Research on alternative fuels has become important due to the increase in the use of gasoline oil resources worldwide and contributed primarily to environmental concerns. Provides solutions for the development of spark ignition (SI) engines using alternative fuels such as compressed natural gas (CNG). The purpose of the research is to explore and understand the combustion phenomena in engines that operate on gas fuel and develop technology as an alternative to today's gas engine technology for heavy duty applications. In this research, CNG had been introduced as an alternative fuel to address environmental problems. However, there was a basic need for mixed formulation studies and spray combustion processes as the type of fuel changes. The pre-combustion chamber design (PCC) had an important influence on engine performance and its knocking properties in engine. The PCC design involves pre-combustion shapes, spark plug locations and inlet and exhaust valves position. To produce higher compression ratio, higher octane number was needed. Therefore, CNG was used to allow incineration without knocking in the engine. The main objective of this investigation is to design, fabricate and included installation of PCC on the SI single cylinder engine that uses natural gas as fuel. In addition, using PCC techniques through experiments to improve engine performance rates and reduce the release of harmful gases while using CNG fuel. Finally, verify all results from simulation and experiments with the same engine specifications. Experiments on single cylinder engine are carried out alongside hydraulic dynamometer as well as some other sensor equipment. The sensors used during the experiment were high pressure sensor, crankshaft angle decoder, gas analyzer, and data analysis acquisition (DAQ). The experiment was conducted based on SAE International standard J1349. The released of HC and CO was better when using CNG than gasoline fuel. The results showed the performance of this single cylinder SI engine when using CNG fuel was reduced against gasoline fuel. However, when PCC was used with CNG fuel, there was an increase in performance output on engine speed. Based on the performance produced by each of these PCCs, PCC 2 has performed better than PCC 1 and PCC 3 for power, torque and work output compared to CNG fuel only. Performance output produced by PCC1, PCC 2 and PCC 3 compared to CNG use without PCC was 5 %, 15 % and 10%. In addition, the results of the ANSYS simulation and experimental results had concluded that the pre-chamber of PCC 2 with CNG use had the best design geometry and higher performance output than PCC 1 and PCC 2. Gas emission levels of O2, CO2, CO, NO, SO2, C3H8 and HC from the experimental results measured by MRU gas analyzer. The use of PCC as well as CNG as a fuel in the engine reduced the release of contaminated gases into the surrounding air compared to the used of gasoline fuel.